تطوير البيئة الريفية وأثرها في حل مشكلة الاسكان - بركات, طارق (Latakia University Journal -Engineering Sciences Series, 2016)
لعب الأثر الفعلي للانتقال الغير مخطط له للبيئة الريفية بمكوناتها المختلفة باتجاه الحضر دوراً كبيراً في إضفاء الصبغة الرمادية على الواقع الإسكاني للمدن السورية عامة، محرراً مشكلة بات حلها أحد أهم الأولويات التي تواجه المخططين من خلال التركيز على امكانية الارتقاء الانتقائي بالمواصفات الايجابية للبيئة الريفية كعامل مساهم وبأثر كبير في حل المشكلة الاسكانية وذلك عبر اقتراح مجموعة من الحلول يمكن أن تسهم عن طريق تطبيقها كأسلوب تنموي ذو صفة ريفية بالحد الفعلي من مشكلة الاسكان. The actual effect of unplanned transition of rural environment with its different components towards urban areas had played a big role in giving the gray tincture on the housing reality of Syrian cities in general, which in turn released a problem that faced planners to solve as one of the most important priorities through concentrating on the possibility of selective elevating of positive specifications of the rural environment as a large effect contributing factor in solving the housing problem through suggesting a group of helping solutions by implementing them as a developing type with a rural quality in actual stopping of housing problem.